2011
DOI: 10.1371/journal.pntd.0001356
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Effectiveness of a Community Intervention for Monkeypox Prevention in the Congo Basin

Abstract: BackgroundIn areas where health resources are limited, community participation in the recognition and reporting of disease hazards is critical for the identification of outbreaks. This is particularly true for zoonotic diseases such as monkeypox that principally affect people living in remote areas with few health services. Here we report the findings of an evaluation measuring the effectiveness of a film-based community outreach program designed to improve the understanding of monkeypox symptoms, transmission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 10 publications
0
43
0
Order By: Relevance
“…Two studies for pandemic influenza took place in high-income countries (Canada7 and Australia6), and one study for monkeypox took place in a low-income country (Republic of the Congo) 28. Both studies of interventions for pandemic influenza took place in 2008, before the 2009 H1N1 pandemic.…”
Section: Results Of Individual Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Two studies for pandemic influenza took place in high-income countries (Canada7 and Australia6), and one study for monkeypox took place in a low-income country (Republic of the Congo) 28. Both studies of interventions for pandemic influenza took place in 2008, before the 2009 H1N1 pandemic.…”
Section: Results Of Individual Studiesmentioning
confidence: 99%
“…Dumais et al reported an educational intervention in a class of 35 female year 10 students in a private school in Canada 7. The intervention in Republic of the Congo was delivered on a much greater scale: approximately 23,860 people in 16 towns and villages received the intervention over a period of 90 days 28. Evaluation was by a survey of 271 people (57% male; mean age 33 years) before and after the intervention 28…”
Section: Results Of Individual Studiesmentioning
confidence: 99%
See 3 more Smart Citations